Effects of Dual-Language Programme (DLP) on the usage of English adjectives by primary school students - Ramli, Rashida Nasuha; Lotfie, Maskanah Mohammad (2018)
The Dual-Language Programme (DLP), which involves the teaching of selected subjects in English, has been widely debated by parents, academics and the public alike. Students from selected schools in Malaysia learn Mathematics and Science in English unlike those who go through the process of learning the subjects in Malaysia’s national language, Malay. As the result of this programme, DLP students are exposed to additional hours of English input compared to non-DLP ones. This paper presents a study that investigates the extent to which the extra hours of English language exposure assist primary school students in grasping the rules and the morphological structures of English adjectives. The differences in the features of adjectives in Malay and English could be one of the main reasons why students face difficulties in comprehending English adjectives. In carrying out this study, data were collated from two classes of standard two involving a DLP and a non-DLP groups (n=54). Two instruments were used and they measured the use of the base form of adjectives as well as comparative ones. t-tests were run on post-test scores to gauge possible significant difference between the mean scores obtained by the control and the experimental groups in terms of the use of those forms. Based on the results for both tests; the Vocabulary Size Test (VST) and the Comparative Adjective Test (CAT), those from DLP group scored higher compared to students from non-DLP group.